2020
DOI: 10.15835/nsb12410651
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative roles of compost on okra (Abelmoschus esculentus L.) exposed to drought stress at vegetative and reproductive growth stages

Abstract: Okra growth and yield are adversely affected by drought at different growth stages. This is aggravated by poor soil fertility. In this study, the roles of compost applied at 0, 5 and 10 t/ha on the tolerance and morpho-physiological response of okra (NHAe 47-4) exposed to varying levels of water stress (25%, 50%, 75% and 100% field capacity, FC), at different growth stages (vegetative, reproductive and vegetative-reproductive stages) for ten days duration were assessed. Data were collected on okra growth and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…However, specifically for the genotype NS7774, the increment was less, indicating it to be a tolerant genotype, whereas others were drought sensitive. ROS production under drought stress has previously been observed in different okra genotypes [ 56 , 57 , 58 ]. In a previous study [ 59 , 60 , 61 ], the investigators showed that MDA levels increased, especially in the susceptible phenotypes, depending on drought stress, and this increase was related to ROS formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, specifically for the genotype NS7774, the increment was less, indicating it to be a tolerant genotype, whereas others were drought sensitive. ROS production under drought stress has previously been observed in different okra genotypes [ 56 , 57 , 58 ]. In a previous study [ 59 , 60 , 61 ], the investigators showed that MDA levels increased, especially in the susceptible phenotypes, depending on drought stress, and this increase was related to ROS formation.…”
Section: Discussionmentioning
confidence: 99%